DAMPAK KEGIATAN PERTANIAN TERHADAP TINGKAT EUTROFIKASI DAN JENIS – JENIS FITOPLANKTON DI DANAU BUYAN KABUPATEN BULELENG PROVINSI BALI - Vivin Nopiantari, Ni Putu; Arthana, I Wayan; Astarini, Ida Ayu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 1 (2017), 2017)
IMPACT OF AGRICULTURAL ACTIVITIES ON EUTROFICATION LEVELS AND TYPES OF FITOPLANKTON IN LAKE BUYAN BULELENG REGENCY PROVINCE OF BALI This research was conducted to find out the impact of agricultural activities in the various levels of eutrophication and diversity of phytoplankton in Buyan Lake, Buleleng, Bali Province. Purposive sampling method was organized to determining research station, where the sampling stations were determined based on various considerations, such as conditions of study area, and predominant use of agricultural land in the study area. Sampling method of phytoplankton and the lake water were done by setting the 4 stations that represent agricultural activities around Buyan Lake. Phytoplankton samples were taken by filtering the water on the lake surface as much as 100 liters, using the plankton net with a mesh size of 25µm. Phytoplankton parameters was analyzed in laboratory. Data was analyzed using analysis of phytoplankton abundance, Equity index and dominance index. Results showed that abundance of phytoplankton at each stations in Buyan Lake was ranged between 1150 – 1791.67 cells / l. Average abundance of phytoplankton in all stations was 1504.17 cells / l. Based on the abundance of phytoplankton, waters of Buyan Lake was classified into water that have low fertility rate (oligotrophic). Agricultural activities around Buyan Lake resulted a moderate eutrophication level (mesotrofik).